Synergistic Role of the Church in Social Action: a Case Study of GBI Jemaat Asia Afrika's Community Service Initiatives - Sasono, Rakhmad Widodo Dwi; Omega, Yuda Putra; Clarissa, Cindy; Herman, Samuel; Hermanto, Yanto Paulus (Jurnal Pengabdian Masyarakat Bestari, 2024)
This community service explores the synergistic role of GBI Jemaat Asia Afrika in society, highlighting its social action initiatives. The method involves surveying target institutions, accurately assessing needs, and announcing plans during church services. Contributions are collected and distributed accordingly. This decade-long initiative targets residents of elderly homes, orphanages, and rehabilitation centers. Success indicators include meeting specific needs and receiving acknowledgment from institution managers. Post-action evaluations ensure continuous improvement. Consistent implementation of these activities demonstrates the church's ability to synergistically fulfill its mission of living, faithfulness, and service, providing meaningful support to the less fortunate and enhancing their sustainability.